Optimization of design variables for rotary regenerative thermal oxidizer high-temperature valve (rto-HTV) based on transient dynamics analysis and multi-objective optimization algorithm - Sun, Bo; Zhao, Tong; Kurnianto Prayitno, Yosephus Ardean; Li, Wei; Sun, Pengzhao; Peng, Cong (AIP Advances, 2021)
The rotary regenerative thermal oxidizer of a high temperature valve (rto-HTV) is repeatedly opened and closed, which causes deformation of the valve page and leads to shortened durability. To prevent the drawback, analysis of impact stress at the moment of rapid collision between the valve page and valve seat is critical. The analysis is focused on optimization of the design variable based on the multi-objective algorithm under transient conditions. To perform transient dynamics, LS-DYNA software is applied for the dynamic analysis of valve page rapid collisions under different initial angular velocities ω. From the LS-DYNA output, the response surface methodology is combined with multi-objective optimization for determining the optimized design variables of the rto-HTV valve page. As a result, the valve page maximum stress (σpage)max is increased with the increase in ω, from (σpage)max = 134 MPa to (σpage)max = 175 MPa. The maximum velocity (vpage)max is increased with the increase in ω, from (vpage)max = 4472 mm/s to (vpage)max = 7475 mm/s. Based on (σpage)max and (vpage)max, the optimization results show that (σpage)max is reduced by 20% and the valve page mass Mpage is reduced by 5%. Moreover, (σpage)max of the optimized valve page is less than the yield strength of 316S at 800 °C. Therefore, the optimization of the valve page is satisfactory and effective for reducing the impact stress between the valve page and valve seat during collision.